Religious Moderates the Influence of Investment Knowledge on Interest in Investing in Green Sukuk - Aulia, Deanti; Hafizi, Muhammad Riza; Mutmainah, Mutmainah; Majeed, Ali Nazar (AL-QARDH, 2024)
Green sukuk are securities whose issuance proceeds are used to finance environmental projects (green projects). The issuance of green sukuk follows the mechanism for issuing state sukuk, as well as the contracts used in the issuance by Sharia principles. This research aims to determine public interest in investing in green sukuk to encourage sustainable development in the financial sector in Indonesia. This research involved 251 respondents from several universities in Central Kalimantan Province as research respondents. Analysis was carried out using partial least squares structural equation modeling with SEM PLS. The findings from the structural model show that the research model is structurally good because it meets all the model criteria. Overall, investment knowledge (KNE) is an important determinant that directs individual decisions to invest in environmentally friendly Sharia financial instruments. Finally, the research findings conclude that religiosity strengthens people's interest in investing in environmentally friendly Sharia financial instruments